A comparative study of the dynamic earthquake behaviour of braced tube, diagrid, tube-in-tube, and shear wall-frame structures - Oduor, Grant; Abuodha, Silvester; Mumenya, Siphila (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
Recent trends show that tubular systems are already popular for tall buildings in most regions of the world; the shear wall-frame system is also dominant in other parts of the globe. This study aimed to compare the dynamic earthquake behaviour of braced tube, diagrid, tube-in-tube, and shear wall-frame structures. This research study used ETABS software to model, analyze, and design 12 building models, whereby every structural system was comprised of 12-, 24-, and 36-story models. The constant model parameters were as follows: the floor slab depth and area, the service area, the plan dimensions, the story heights, and materiality. The research used modal response spectrum analysis per EN 1998-1-1:2004 for the Nairobi city area in Kenya to obtain the fundamental periods of vibration, top drifts, seismic base shears, and top floor accelerations of the braced tube, diagrid, tube-in-tube, and shear wall-frame models. The dynamic earthquake behaviour of the aforementioned lateral systems with different heights is illustrated. The study recommends the use of diagrid systems for seismic load resistance in 12-, 24-, and 36-story buildings with regular plan geometry. Keywords: Fundamental period of vibration, top drift, seismic base shear, top floor acceleration, modal response spectrum analysis, tall buildings.